KEMAMPUAN KEUANGAN NEGARA DALAM PERSPEKTIF PEMENUHAN ANGGARAN DAN KEBIJAKAN SEKTOR PENDIDIKAN - Ariesy Tri Mauleny; Achmad Sani Alhusain (Jurnal Ekonomi & Kebijakan Publik, 2010)
State Budget (APBN) becomes the main instrument of the government to manage the income and spending of the country to reach welfare’s people. Therefore it needs join understanding between parliament and government in order to implement 'checks and balances' to the effective, and efficient. This is due the instrument of welfare like the budget funds for education still low, altaough the budget reachedf 20% to total budget based as mandated by the Constitution. This study aims to explore the constitutional mandate for education budget, in which this study shows that, basically, the state has able to allocate 20% for education sector as seen from the trend of increasing state revenue. However, this trend likely is always accompanied by the increase in spending that is resulted by a deficit budget policy. Therefore, DPR and the government needs a commitment to prioritise the budget each year through budget planning, controlling and accountability in the use of the budget of education.